Coronal alignment in total knee arthroplasty and its effect on functional outcome: A retrospective study - Maharjan, Promish; Chen, Wang; Dong, Guo Yu; Zheng, Wang Shang (Grande Medical Journal, 2024)
Background This retrospective study was conducted to compare the coronal alignment of the lower extremity before and after surgery in patients undergoing total knee replacement by assessing the mechanical axis in the full-length weight-bearing radiograph taken preoperatively and post-operatively, and to assess the clinical outcome after TKA with reference to the mechanical axis.Method Fifty eight patients who underwent primary TKA from date October 2013 to March 2017 were included in the study. The patient’s demographics such as age, gender primary TKA were noted. All patients underwent clinical and radiological evaluation, including standardized radiographs (anterior-posterior long-leg X-ray). For clinical outcome scoring the Hospital for Special Surgery score (HSS) and Western Ontario and McMaster Universities Arthritis Index (WOMAC) were used. One-way ANOVA was used to compare the outcome of the surgery and the alignment (p